'Read it, now what? Engaging students with information literacy'. Issue 2 (10th August 2020) - Foord, Karen
Abstract : Purpose: The purpose of this action research study was to explore whether enabling work-based students to identify their information literacy (IL) needs and participate in activity design would increase their IL and enhance their academic performance. Design/methodology/approach: Initially students reflected on their own knowledge, skills and engagement with IL. Next, they identified aspects of IL that challenged them. Students worked in small groups to identify tasks and activities to enhance their skills. They completed practical IL tasks during a taught session. A scoring rubric assessed student engagement with IL. Concurrently a qualitative questionnaire was developed and used to explore the student experience of the intervention. Findings: The study found that students did engage with information literacy and there was an improvement in the pass rate from previous cohorts. The qualitative analysis demonstrated that students felt that the interaction had benefitted their engagement with IL and their learning and understanding as a result. Research limitations/implications: This study was a small study at one higher education institution and cannot therefore be considered generalizable. It does nevertheless provide valuable insights in terms of student engagement with IL. Practical implications: This study influenced the delivery of the subsequent modules. It has the potential to influence the delivery of information literacy skills on health and social care apprenticeships. Originality/value: This paper adds to the literature exploring the relationship between students and information literacy. Enhancing the discourse from the instructor perspective rather than that of the information professional.